PHRASAL VERBS FOUND IN NOVEL â€œTHEY BOTH DIE AT THE ENDâ€ BY ADAM SILVERA - Sayu Putu Ratih Kumara Devi; I Nyoman Kardana; Dewa Ayu Dyah Pertiwi Putri (Universitas Warmadewa, 2023)
The title of this research is â€œPhrasal Verbs Found in Novel â€œThey Both Die at The Endâ€ By Adam Silveraâ€. The data source of this research is the novel They Both Die at The End by Adam Silvera (2017). The problems investigated in this research are; what kind of phrasal verbs and what constituent structures are used for phrasal verbs in Adam Silveraâ€™s They Both Die at The End? The theories applied are by Halliday and Matthiessen about phrasal verbs, and by Van Valin about tree diagrams. This research used the qualitative method. This research consisted of three steps. The first step was reading the novel. Furthermore, the data collection was conducted by note-taking. After that, the data were classified into their kind and their constituent structure. The result of the research showed that three kinds of phrasal verbs were found in Adam Silveraâ€™s They Both Die at The End. The kinds are verb + adverb, verb + preposition, and verb + adverb + preposition. The constituent structure of each sentence with phrasal verbs showed that phrasal verbs can be transitive and intransitive. Transitive phrasal verbs mean that it requires a direct object. Transitive phrasal verbs can be separable which means the verb and particle are separated by a noun, and inseparable which means the verb and particle cannot be separated by a noun. Keywords: constituent; kind; phrasal verbs